Health benefits of fermented foods and beverages - Tamang, Jyoti Prakash (CRC Press, Taylor & Francis Group, 2015)
Functional Microorganisms in Fermented Foods and Beverages. Therapeutic Values of Fermented Foods: Traditional Concept and Scientific Claims. Health Benefits of Fermented Vegetables Products. Health Benefits of Fermented Legume Foods. Health Benefits of Fermented Cereal Foods. Health Benefits of Fermented Milk Products. Health Benefits of Fermented Fish Products. Health of Fermented Meat Products. Health Benefits of Alcoholic Beverages. Health Benefits of Wine. Health Benefits of Yogurt. Health-Promoting Benefits of Fermented Tea and Coffee. Saponin as Health-Promoting Bio-active Compounds in.